Rescue therapeutic strategy combining ultra-protective mechanical ventilation with extracorporeal CO2 removal membrane in near-fatal asthma with severe pulmonary barotraumas: A case report. Issue 41 (October 2017) - Pavot, Arthur; Mallat, Jihad; Vangrunderbeeck, Nicolas; Thevenin, Didier; Lemyze, Malcolm
Abstract: Rationale: Mechanical ventilation of severe acute asthma is still considered a challenging issue, mainly because of the gas trapping phenomenon with the potential for life-threatening barotraumatic pulmonary complications. Patient concerns: Herein, we describe 2 consecutive cases of near-fatal asthma for whom the recommended protective mechanical ventilation approach using low tidal volume of 6 mL/kg and small levels of PEEP was rapidly compromised by giant pneumomediastinum with extensive subcutaneousemphysema. Diagnoses: Near fatal asthma. Intervention: A rescue therapeutic strategy combining extracorporeal CO2 removal membrane with ultra-protective extremely low tidal volume (3 mL/kg) ventilation was applied. Outcomes: Both patients survived hospital discharge. Lessons: These 2 cases indicate that ECCO2 R associated with ultra-protective ventilation could be an alternative to surgery in case of life-threatening barotrauma occurring under mechanical ventilation.